Evolving Diagnostic and Treatment Strategies for Pancreatic Neuroendocrine Tumors - Kulke, Matthew H (BioMed Central, 2011)
Pancreatic neuroendocrine tumors (NET) have diverse clinical presentations. Patients with symptoms of hormone secretion may require specific medical interventions to control those symptoms prior to antitumor intervention. In some patients, tumors in the pancreas may be occult and specialized diagnostic imaging or surgery may be required for diagnosis. Other patients may present with more advanced disease, presenting with symptoms of tumor bulk rather than hormone secretion. Treatment options for patients with advanced pancreatic neuroendocrine tumors include surgical resection and hepatic directed therapies, including partial hepatectomy, hepatic artery embolization, or other ablative techniques. Streptozocin or temozolomide-based chemotherapy regimens are active against pancreatic NET, and can also play an important role in the palliation of patients with advanced disease. A number of biologically targeted agents targeting the VEGF and mTOR signaling pathways have recently shown promise, with recent trials showing treatment with the VEGFR tyrosine kinase inhibitor sunitinib or the mTOR inhibitor everolimus improves progression-free survival in patients with advanced NET.